Work-related musculoskeletal disorder (WMSDs) and functional status of firefighters in Klang Valley/ Nur Liyana Aqilah Mohd Azmi and Mohamad Ghazali Masuri - Mohd Azmi, Nur Liyana Aqilah; Masuri, Mohamad Ghazali (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Firefighters have high risk to get work-related musculoskeletal disorders (WMSDs) due to great physical demands needed in their duty. The purpose of this cross-sectional study was to investigate the WMSDs and functional status of firefighters in Klang Valley. A total of 101 respondents from three Fire and Rescue Department in Klang Valley completed two self-rated assessments which were The Malay Version of Cornell Musculoskeletal Discomfort Questionnaires (CMDQ-M) and COOP/WONCA Chart. Lower back had been found to have the highest WMSD prevalence among all the body regions examined. The multiple regression test identified WMSDs at the upper back, lower back, left wrist, and left thigh have significant relationship with 50% of the aspects of functional status. In addition, the multiple regression test also revealed that WMSDs at the right arm, left wrist, right thigh, left calf and left knee appeared to become the main factor contributing to each aspect of functional status. By using independent sample T-test, age, smoking status, back pain history, working experiences, and exercise routine had been revealed as the factors associated with increased of WMSDs symptoms. WMSDs were disabling and potentially disruptive to the firefighters’ functional status.